The Invalidity of International Treaties and Jus Cogens - Sandorski, Jan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Nieważność umów międzynarodowych by Jan Sandorski, published originally in Polish in 1978. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.